UTILIZATION OF POPPY SEEDS (PAPAVER-SOMNIFERUM) AND SESAME SEEDS (SESAMUM-INDICUM) FOR DEVELOPMENT OF NUTRIA-ENRICHED SNACKS - Virginia, Paul (Indian Journal of Community Health, 2015)
Poppy seeds and sesame seeds are good source of carbohydrate, calcium, and energy. Poppy seeds and sesame seeds is rich in vitamin C, Vitamins B1, B2, E, Fiber and calcium. It reduces the risk of cataract, heart disease and cancer. Poppy seeds are especially rich in Oleic and Linoleic acids. Oleic acids monosaturated fatty acids help lower LDL or “bad cholesterol” and increases HDL or “good cholesterol” levels in the blood. Sesame seeds contain a high quality protein, rich in soluble fiber. The combination of the oil and the fiber makes sesame seeds ideal laxative. The present research was conducted with the objective to develop nutrient dense products from a combination of poppy seeds and sesame seeds to assess their sensory properties and to determine the nutritive value of the prepared products. Organoleptic evaluation was carried out using nine point hedonic scales. Nutritive value was calculated by using food composition tables given by ICMR. On the basic of findings, it was observed that in case of Idli, Biscuits and Chutney the treatment T2 (20% incorporation of poppy seeds and sesame seeds) found best in all sensory parameters colour, texture, taste and overall acceptability. For halwa and Dhokla the treatment T1 (15% incorporation of poppy seeds and sesame seeds) found best in all sensory parameters. Halwa was rich in energy and calcium content (447.4kcal/100kcal and 477.5mg/100g) respectively. Idli was highest in energy (340kcal/100kcal, calcium, 637.2mg/100g).Dhokla was rich in energy and calcium content (333.6kcal/100kcal, 580.1g/100g) and Chutney was rich in energy and calcium content (433.6kcal/100kcal and 611.3mg/100g) respectively. Biscuit was rich in energy and calcium content (456.3kcal/100kcal and 616.8/100g).The cost of the products ranged between Rs 18.5 for Halwa, Rs 20.68 for Idli, Rs. 19.49 for Dhokla, Rs. 22.04 for Chutney, Rs. 20.84 for Biscuit per 100g of dry ingredients.